TILL WORK DO US PART - THE SOCIAL FALLACY OF LONG-DISTANCE COMMUTING - Erika Sandow (European Regional Science Association (ERSA), 2010)
A growing number of people in Europe are long-distance commuters. For some people and households long-distance commuting may be a temporary lifestyle, offering financial and career benefits, whereas for others commuting lifestyle becomes permanent. Commuting can mean increased salary, a better job, the only possibility to keep a job for the individual, but also increased stress, long travel times, and in some cases household break-up. However, despite the growing number of long-distance commuters, the long-term social implications of long-distance commuting on households are not well understood. This paper focuses on social implications of long-distance commuting on commuters and their households in Sweden. Discrete-time regression models were employed to register data on Swedish couples in 2000 to explore the risk of separation following long-distance commuting during 1995 to 2005. The results show that among couples where one or both spouses long-distance commute separation rates are higher compared to non-commuting couples. For men the odds of separating are highest if commuting is on a temporary basis, whereas women decrease the odds when continuing commuting for a longer time-period.
Keywords: 330; long-distance commuting; household breakup; longitudinal study